Atuação das Organizações da Sociedade Civil (OSCS) em Manaus na política pública da criança e do adolescente - Costa, Roberta Justina da (2018)
In this contemporary scenery, the changes in the capitalist production way in the State and in the Civil Society alter the society manner worldwide, standing out specially in the settings presented in public policies provision, flagged for several societal segments in their pursuit for the social rights effectuation. In this context, the non state–owned public sphere build itself in a privileged space, a stage of disputes, interests and the social participation in the matter of social projects and social programs furtherance. It deals with an area that, historically, takes part on the social demands and, above all, nowadays, is intensifying its engagement in the State and Organized Civil Society articulated network in the social public policies process of elaboration, implementation and control. The present study, thereby, has as a research problem: How the Civil Society Organizations (CSOs), that represent the non state–owned public sphere, act with the child and adolescent policies in the city of Manaus? Having as a general objective to analyse how the Civil Society Organizations act in the public policy for child and adolescent in Manaus/AM, seeking to uncover how the non state–owned public sphere adresses in the social services assets coproduction. The research methodological course presents a qualitative approach, centering around five CSOs, that develop activities with children and adolescents in Manaus, and as a research subjects, five managers and ten users. The results point out that the CSOs are configured in accordance with the 10.406/2002 law (juridical people of private right without lucrative purposes); due to its purpose, they follow the axis of social protection basis with the prevention and social rights promotion; the participation of the non state–owned public sphere in the enlarged spaces of discussion is relevant for their development, in spite of the social control fragility in Brazilian society; in the range of social services instalments in the Manauara society, it is figured out that the exigencies for the CSOs are increasing more and more for the great part of the citizens in their demands and necessities; faced with the deterioration of the social expressions issues, it becomes blatant that the State primacy is crucial in this matter; and the CSOs presence in the political debate of the public policies with the efervescent non state–owned public sphere as the locus of struggle and resistence for the social rights concretion. As for conclusion, the Civil Society Organizations, participants of the non state–owned public sphere, are located in a complex and contradictory public space, permeated for several social actors performing in a political arena of intervention, dispute, struggle and construction of the possible concepts in the conjunction of the political society with the civil society, as for the elaboration, enforcement or social control that, lined in the pursuit for the citizenship, constitute the basis for the contemporary management operation.